The Role of Internal Audit in Strengthening Corporate Governance - Charisma Kuriata Ginting Suka; Ika Wulandari; Fudji Sri Mar’ati; Erna Sudarmawanti (CV. Ulil Albab Corp, 2025)
This study aims to examine the role of internal audit in strengthening Corporate Governance through a literature review of various academic research and professional practices. In an increasingly complex business environment, internal audit plays a crucial role in ensuring compliance, transparency, and the effectiveness of a company's internal controls. This study uses a qualitative method by reviewing relevant scientific articles, to identify the contribution of internal audit to corporate governance principles such as accountability, transparency, and risk management. The results of the study indicate that internal audit has a significant impact on improving the quality of governance, assisting management in decision-making, and strengthening the Company's internal oversight and regulatory compliance. This study also recommends strengthening the role of internal auditors in the organizational structure and the need for further research to develop an internal audit model that is adaptive to the dynamics of corporate governance in Indonesia.